2016
DOI: 10.17344/acsi.2016.2842
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Synthesis of Zinc Borates from a Zinc Oxide Precursor via Ultrasonic Irradiation

Abstract: In this study, zinc borate hydrate (Zn 3 B 6 O 12 · 3.5H 2 O) was synthesized from zinc oxide (ZnO) and boric acid (H 3 BO 3 ) via a novel method of ultrasonic irradiation. X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FT-IR) and Raman spectroscopy were used to characterize the synthesized products. Scanning electron microscopy (SEM) was used to determine the effects of reaction time and reaction temperature on the morphology of the products. Thermal dehydration kinetics were studied using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 19 publications
4
9
0
Order By: Relevance
“…The compounds' XRD patterns with the highest XRD scores are given in Figure 2. The characteristic peaks are in mutual agreement with the studies reported in the literature (Ersan et al, 2016;Kipcak et al, 2014Kipcak et al, , 2015Kipcak et al, , 2016Vardar et al, 2017). In addition, the as-obtained XRD scores were slightly higher than those previously reported in the literature (Table 1).…”
Section: The As-synthesized Zinc Borate Compounds' Xrd Results and Thsupporting
confidence: 90%
See 2 more Smart Citations
“…The compounds' XRD patterns with the highest XRD scores are given in Figure 2. The characteristic peaks are in mutual agreement with the studies reported in the literature (Ersan et al, 2016;Kipcak et al, 2014Kipcak et al, , 2015Kipcak et al, , 2016Vardar et al, 2017). In addition, the as-obtained XRD scores were slightly higher than those previously reported in the literature (Table 1).…”
Section: The As-synthesized Zinc Borate Compounds' Xrd Results and Thsupporting
confidence: 90%
“…According to the XRD results, the as-synthesized compound was defined as "zinc oxide borate hydrate (Zn 3 B 6 O 12 •3.5H 2 O)" with the pdf No. "00-035-0433" and was identical to that previously reported in the literature (Bardakci et al, 2013;Ersan et al, 2016;Kipcak et al, 2014Kipcak et al, , 2015Kipcak et al, , 2016Vardar et al, 2017). The as-synthesized zinc borate compound's XRD results are given in Figure 1.…”
Section: The As-synthesized Zinc Borate Compounds' Xrd Results and Thsupporting
confidence: 79%
See 1 more Smart Citation
“…The bands from 1190 cm -1 to 1120 cm -1 correspond to the stretching vibration of the boronoxygenhydrogen [δ(B-O-H)] [25]. The bands between 860 cm -1 and 800 cm -1 correspond to the asymmetric stretching vibration of the four-coordinate boron to oxygen bands [ν as (B 4 -O)] [26].…”
Section: Crystalline and Morphological Characterization Of Nanoflowermentioning
confidence: 99%
“…The band of ν as (B 4 -O) appears at 1048 cm −1 , meanwhile the band of νp(B(OH) 4 ) is observed at approximately 755 cm −1 . Moreover, the peak at 664 cm −1 is assigned to the bending of γ(B 3 -O), the peak of δ (B 4 -O) appears at around 578 cm −1 , and the peak at 297 cm −1 corresponds to the bending of B 3 -O [26].…”
Section: Crystalline and Morphological Characterization Of Nanoflowermentioning
confidence: 99%